2019
DOI: 10.1152/ajpcell.00235.2019
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of the neonatal Fc receptor in cultured podocytes alters IL-6 signaling and the actin cytoskeleton

Abstract: The neonatal Fc receptor (FcRn) has been shown to be required for antigen presentation in dendritic cells, and global knockout of FcRn attenuates immune-mediated kidney disease. Podocytes express interleukin-6 (IL-6) receptor and produce IL-6 under proinflammatory conditions. Here we examined the role of FcRn in the IL-6-mediated inflammatory response in podocytes. We examined IL-6 production by ELISA and expression by qPCR in wild type (WT) and FcRn knockout (KO) podocytes after treatment with proinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…FcRn KO podocytes are also hypermotile at baseline and have significantly shorter stress fibers. These defects can be rescued by treatment with IL-6 [ 205 ]. FcRn-mediated modulation of the actin cytoskeleton via IL-6 provides further evidence that protein trafficking in podocytes is linked to actin cytoskeletal dynamics.…”
Section: Other Mediators Of Podocyte Actin Dynamicsmentioning
confidence: 99%
“…FcRn KO podocytes are also hypermotile at baseline and have significantly shorter stress fibers. These defects can be rescued by treatment with IL-6 [ 205 ]. FcRn-mediated modulation of the actin cytoskeleton via IL-6 provides further evidence that protein trafficking in podocytes is linked to actin cytoskeletal dynamics.…”
Section: Other Mediators Of Podocyte Actin Dynamicsmentioning
confidence: 99%
“…The exact mechanisms by which the absence of FcRn prevents crescent formation may have to do with impaired podocyte mobility, alterations in actin dynamics or impaired intracellular signaling. The mechanism underlying how FcRn may affect these pathways is unknown but we have found that knockout of FcRn KO in cultured podocytes alters mobility and actin dynamics (37). In addition, when comparing the relative quantity of the crescents between the two models, we found significantly fewer glomeruli in the anti-GBM had crescents compared to the NTS model, which is suggestive that crescent formation is more dependent on the autologous phase than the heterologous phase of immune mediated kidney disease.…”
Section: Discussionmentioning
confidence: 76%
“…Cell culture: Generation of conditionally immortalized WT and FcRn KO podocytes: Podocytes were isolated from WT or global FcRn KO mice and then underwent immortalization using a thermosensitive polyomavirus simian virus 40 (SV40) T antigen as previously described. (35)(36)(37) Primary podocytes were allowed to replicate at 33 o C. To induce differentiation, podocytes were placed at 37 o C for 8 -10 days. To verify expression of podocyte markers, podocytes were stained with podocin or WT1 and synaptopodin expression was checked by Western blot.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations